KOMPETENSI APARATUR DESA DALAM MEWUJUDKAN OTONOMI DESA DI DESA MEKARSARI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI - Amiddana Bilhidayah; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Government in realizing the welfare of society, through public services that are still less than optimal. One of the causes is the less competent village apparatus in carrying out their duties and training carried outby the villageapparatus must be inaccordance with the training in general that is implemented so as to produce quality human resources. The purpose of this study is to describe and know the competencce of the village apparatus in realizing village and to know the factor that influnce the competence of village apparatusin Mekarsari village. This method used in this research is qualitative method. The data sources is taken from the primary and secondary data. Data collection techniques used interview techniques. Observation and documentation. The information is village head, village secretary, head of village affairs and society, while data analysis technique used in this research is descriptive qualitative analiysis. Basedon the results of the research note that the competence of the village apparatus in realizing village autonomy in the village of Mekarsari is good. This is evidenced by the data of observations and interviews on aspects of knowledge, skills, attitudees in the apparatus of Mekasrari village. The knowledge possessed by the Mekasrasi village apparatus is wellknown from the knowledge of the main tasks and functions. The skills of the Mekarsari village apparatus are also good in the implementation of village autonomy. Mekarsari village has a good attitude in inviting the community to participate in the implementation of village autonomy, but less optimalin service and less able to interact with the community. Factor influencing the competence of Mekarsari village apparatus in the participation of the village community and the absence of operational standard procedure. Keywords : Competence and Village Autonomy